Mapping and Analysis of Stunting Risk Factors in East Java - Nisaul Khoiro, Rahmi Alfiyanti; Fajriyah, Izzatul (Journal La Medihealtico, 2025)
The prevalence of stunting in East Java Province was recorded at 17.7%, where this figure has been below the maximum limit of the WHO stunting prevalence, but still has not reached the Ministry of Health's performance target. The purpose of this study is to provide information about the distribution of stunting cases and their risk factors visually through maps, as well as to identify factors that affect the prevalence of stunting in East Java Province in 2023. This study uses a quantitative research design with cross sectional. The population in this study is districts/cities in East Java Province in 2023, which is 38 districts/cities. The sample in this study is the entire total population. The analysis used was multiple linear mapping and regression, using GeoDa software. The mapping results showed that the highest prevalence of stunting was found in Jember Regency, Lumajang Regency, Probolinggo Regency, and Probolinggo City. The results of the multiple linear regression test showed that the percentage of exclusive breastfeeding in infants < 6 months significantly (p=0.01227) had an effect on reducing the prevalence of stunting. Population density (p=0.09750), number of posyandu (p=0.94130), percentage of households with access to healthy latrines (p=0.76093), and number of villages/sub-districts with 5 STBM pillars (p=0.9414) did not have a significant effect on reducing the prevalence of stunting. It is hoped that the results of this study can be used to develop more effective intervention programs in reducing the prevalence of stunting in East Java Province, such as focusing on exclusive breastfeeding in 1,000 HPK.